2023
DOI: 10.1186/s40001-023-00997-9
|View full text |Cite
|
Sign up to set email alerts
|

[68Ga]Ga-FAPI-04 PET MRI/CT in the evaluation of gastric carcinomas compared with [18F]-FDG PET MRI/CT: a meta-analysis

Abstract: Objectives To compare the detection rates of [68Ga]Ga-FAPI-04 PET MRI/CT vs. [18F]-FDG PET MRI/CT in gastric cancer. Methods An extensive librarian-led literature search of PubMed, Embase, Web of Science, the Cochrane Central Library, and ClinicalTrials.gov was performed. The primary outcomes were sensitivity in patient-based evaluations, detection of lymph node metastases, and peritoneal involvement. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 23 publications
2
8
1
Order By: Relevance
“…Our systematic review, which gathers original studies on GC from 2018 onwards, provides strong clinical evidence to support the superior diagnostic sensitivity of 68 Ga-FAPI over 18 F-FDG for identifying primary tumours, recurrent tumours, lymph node infiltration, and distant metastases. In contrast to the previous meta-analysis 51 , 52 , our study brings forth some important nuances and enhancements. For one, we presented the comparative results and a subgroup analysis of the diagnostic accuracy of 68 Ga-FAPI versus 18 F-FDG PET/CT in gastric cancer, which was not extensively covered in previous work.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Our systematic review, which gathers original studies on GC from 2018 onwards, provides strong clinical evidence to support the superior diagnostic sensitivity of 68 Ga-FAPI over 18 F-FDG for identifying primary tumours, recurrent tumours, lymph node infiltration, and distant metastases. In contrast to the previous meta-analysis 51 , 52 , our study brings forth some important nuances and enhancements. For one, we presented the comparative results and a subgroup analysis of the diagnostic accuracy of 68 Ga-FAPI versus 18 F-FDG PET/CT in gastric cancer, which was not extensively covered in previous work.…”
Section: Discussioncontrasting
confidence: 82%
“…Additionally, we calculated and compared the SUVmax and TBRs derived from these two PET scans, providing more depth to our results. Significantly, our study involves a larger patient population than Wang's study 51 , encompassing 358 patients as opposed to 148, adding robustness to our findings. We also have observations on the diagnostic accuracy for lymph node metastases.…”
Section: Discussionsupporting
confidence: 63%
“…2 A-B). A meta-analysis including 5 studies, confirmed the higher sensitivity of FAPI PET over FDG PET in detection of primary tumour (100% vs. 84.43%), lymph node metastases (81.97% vs. 67.21%), and peritoneal metastases (100% vs. 44.74%) of gastric cancer [ 52 ].
Fig.
…”
Section: Fap-targeted Imaging In Gastrointestinal Oncologymentioning
confidence: 91%
“…Numerous studies have established a correlation between active aerobic glycolysis and the onset and progression of gastric cancer, with several molecular mechanisms being implicated [ 5 ]. In a prior investigation, glucose uptake in patients with stomach cancer was assessed by F-fluorodeoxyglucose (FDG)-PET, and all gastric malignancies with high levels of Glut-1 showed improved glucose uptake, with the exception of signet-ring cell carcinoma [ 6 ]. In addition, DNA polymerase is also thought to be involved in maintaining mitochondrial homeostasis.…”
Section: Introductionmentioning
confidence: 99%